2002
DOI: 10.1136/bmj.325.7374.1214
|View full text |Cite
|
Sign up to set email alerts
|

Nurse telephone triage for same day appointments in general practice: multiple interrupted time series trial of effect on workload and costs

Abstract: Objective To compare the workloads of general practitioners and nurses and costs of patient care for nurse telephone triage and standard management of requests for same day appointments in routine primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
119
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(125 citation statements)
references
References 14 publications
2
119
0
1
Order By: Relevance
“…23 In triage of same day appointment requests, CDSS use led to a decrease in GP appointments (risk difference 0.23, 95% CI 0.20 -0.26, p = 0.00). 25 In out-of-hours telephone triage, there was a reduction in adverse events in the intervention group, with a significant difference in two of the four measures. 23 The upper 95% confidence interval for the number of deaths within 7 days of contact with the service in the intervention arm was well within the limits of equivalence (risk difference 0.00, 95% CI 0.00 -0.00, p=0.48).…”
Section: Cdss (4 Rcts 1 Its 19744 Participants)mentioning
confidence: 99%
See 3 more Smart Citations
“…23 In triage of same day appointment requests, CDSS use led to a decrease in GP appointments (risk difference 0.23, 95% CI 0.20 -0.26, p = 0.00). 25 In out-of-hours telephone triage, there was a reduction in adverse events in the intervention group, with a significant difference in two of the four measures. 23 The upper 95% confidence interval for the number of deaths within 7 days of contact with the service in the intervention arm was well within the limits of equivalence (risk difference 0.00, 95% CI 0.00 -0.00, p=0.48).…”
Section: Cdss (4 Rcts 1 Its 19744 Participants)mentioning
confidence: 99%
“…23,25 Characteristics of these studies are given in Table 6 and the results are reported in Table 7.…”
Section: Cdss (4 Rcts 1 Its 19744 Participants)mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several countries proposed changes to primary care organization (1,2).Thus, there has been an increase in the use of telephone consultations (3)(4)(5). Telephone consultations can reduce both the emergency care visits and the number of visits overtime for general practitioners (GPs) (3)(4)(5).Moreover, the availability of telephone consultations in primary care could effectively reduce costs (6).In the literature, there is evidence that telephone consultations guarantee patient safety (7)(8)(9) and user satisfaction (3,10).…”
Section: Introductionmentioning
confidence: 99%